Pengaruh Label Syariah pada Hotel Terhadap Jumlah Pengunjung Hotel Sri Indrayani Pekanbaru - Ika Ernita Sari; Husni Fuaddi; Yahanan Yahanan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research was appointed with the background of the hospitality business which has developed into two, namely conventional and sharia hotels. In the conventional way, it can be successful, but if you lose, you will really lose but get a reward from Allah SWT. Based on the limitations of the existing problems, the formulation of the problem in this research is: What are the sharia indicators that are practiced at Sri Indrayani hotel? How does the use of sharia labels in hotels affect the number of visitors to Sri Indrayani hotels? This research uses primary data, namely data obtained directly from the object to be studied. And secondary data is obtained by certain institutions or institutions, such as bureaus and others. In this study, the subject is hotel managers and hotel visitors, the object is the influence of sharia labels on the number of visitors to Sri Indrayani Pekanbaru hotel. The population in this study were visitors and employees of Hotel Sri Indrayani Pekanbaru, amounting to 41 people. The results of the study show that the Sharia indicators implemented at the Sri Indrayani Hotel Pekanbaru are not accepting non-mahram couples and not providing non-halal food. Based on the research that has been done by reviewing the terms and conditions of the Sri Indrayani Hotel Pekanbaru, it can be explained that the conditions are in accordance with Islamic law. And the effect of the use of the sharia Lbel at the Sri Indrayani Hotel Pekanbaru, namely that visitors who stay stay calm and increase in many ways from year to year, visitors who stay are increasing.